Simultaneous extraction of phosphatidylcholine and phosphatidylethanolamine from soybean lecithin. Issue 10 (30th March 2015) - John, Johnson V.; Park, Huiju; Lee, Hye Ri; Suh, Hongsuk; Kim, Il
<x xml:space="preserve">Abstract</x> A high composition of phosphatidylcholine (PC) and phosphatidylethanolamine (PE) was simultaneously extracted from soybean lecithin by using a mixed solvent consisting of ethanol and chloroform. The addition of chloroform in ethanol improved the total extraction yield to give high a composition of PC and PE. Thus, the best extraction yield (52%) of PC and PE was achieved at an ethanol/chloroform ratio of 6/4 (v/v). Molecular dynamics calculations of the amorphous cell bearing PC, PE, and solvent molecules were performed in order to understand the distribution of PC and PE molecules in specific solvent conditions. The extraction yield was also sensitive to extraction temperature, time and liquid to solid ratio. The extracted PC and PE mixture was successfully purified by flash chromatography using chloroform/methanol (8/2 v/v) as eluting solvent. The purified yields of PE and PC from lecithin extract were 16 and 35%, respectively. The structure of the extracted products was characterized by thin‐layer chromatography and 1H, 13C, 31P NMR, FTIR and UV/vis spectroscopies, and elemental analysis. The purity of PE and PC was higher than 95%. Practical applications: Lecithin composed of phosphoric acid, choline, fatty acids, glycerol, glycolipids, triglycerides, and phospholipids is widely used in human food, animal feed, pharmaceuticals, paints, and other industrial applications. Lecithin can easily be extracted chemically using various solvents in order to obtain pure components. Due to the importance of phospholipids there have been a number of reports on the extraction of PC from lecithin; however, there have been few reports on the extraction of PE or the simultaneous extraction of PC and PE. Thus the simultaneous extraction of PC (35%) and PE (16%) from soybean lecithin by using a mixed solvent consisting of ethanol and chloroform can be a good example to obtain such components in high yields. The protocol employed here is quite straightforward so that pure PC and PE can be obtained economically and may attract interest on mixed solvent systems for the simultaneous extraction of lecithin components. <inline-graphic xlink:href="ark:/27927/pgkfn975vt" content-type="ejlt201400396-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> Phosphatidylcholine and phosphatidylethanolamine were simultaneously extracted from soybean lecithin by using a mixed solvent consisting of ethanol and chloroform.